Agriculturas urbanas em São Paulo: histórico e tipologia - Eduardo de Lima Caldas; Martin Jayo (Confins)
This article aims to contribute to the knowledge on contemporary policies and practices of urban agriculture in the city of São Paulo. With this purpose, we trace the history of urban agriculture in São Paulo from the 1980s, and analyze the current agricultural practices which result from such history. The study reveals that initiatives and policies have historically oscillated between two distinct forms of urban agriculture: one of them “scale oriented”, the other “visibility oriented”. These two models, each of whom results from a different articulation of actors and attributes different meaningsto urban agricultural practices, coexist nowadays in the city, despite being practiced in different areas: “scale oriented” agriculture is generally located in peripheral areas, whereas “visibility oriented" agriculture concentrates in more central regions.